2001
DOI: 10.1182/blood.v97.4.1009
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of HIF-1α under the influence of nitric oxide

Abstract: The key player for adaptation to reduced oxygen availability is the transcription factor hypoxia-inducible factor 1 (HIF-1), composed of the redox-sensitive HIF-1alpha and the constitutively expressed HIF-1beta subunits. Under normoxic conditions, HIF-1alpha is rapidly degraded, whereas hypoxia, CoCl(2), or desferroxamine promote protein stabilization, thus evoking its transcriptional activity. Because HIF-1 is regulated by reactive oxygen species, investigation of the impact of reactive nitrogen species was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
176
2
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(200 citation statements)
references
References 33 publications
20
176
2
2
Order By: Relevance
“…Initial observations suggested that NO inhibits hypoxia-induced HIF-1␣ stabilization and HIF-1 transcriptional activation (Liu et al, 1998;Sogawa et al, 1998;Huang et al, 1999). More recent studies indicated that chemically diverse NO donors or enhanced endogenous NO formation by inducible NO-synthase or NO formation in a coculture system under normoxic conditions provoked HIF-1␣ stabilization, HIF-1 DNA-binding, and activation of downstream target gene expression (Kimura et al, 2001;Sandau et al, 2001aSandau et al, , 2001bZhou et al, 2003). Studies performed in several cell systems such as tubular LLC-PK 1 , human glioblastoma, human hepatoma, or bovine pulmonary artery endothelial cells imply that this is neither species specific nor restricted to certain cell types.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial observations suggested that NO inhibits hypoxia-induced HIF-1␣ stabilization and HIF-1 transcriptional activation (Liu et al, 1998;Sogawa et al, 1998;Huang et al, 1999). More recent studies indicated that chemically diverse NO donors or enhanced endogenous NO formation by inducible NO-synthase or NO formation in a coculture system under normoxic conditions provoked HIF-1␣ stabilization, HIF-1 DNA-binding, and activation of downstream target gene expression (Kimura et al, 2001;Sandau et al, 2001aSandau et al, , 2001bZhou et al, 2003). Studies performed in several cell systems such as tubular LLC-PK 1 , human glioblastoma, human hepatoma, or bovine pulmonary artery endothelial cells imply that this is neither species specific nor restricted to certain cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed in several cell systems such as tubular LLC-PK 1 , human glioblastoma, human hepatoma, or bovine pulmonary artery endothelial cells imply that this is neither species specific nor restricted to certain cell types. Guanylyl cyclase antagonists and lipophilic cGMP analogues did not attenuate/mimic HIF-1␣ accumulation and thus excluded a role of the soluble guanylyl cyclase-cGMP pathway (Kimura et al, 2000;Palmer et al, 2000;Sandau et al, 2001a), thus leaving molecular mechanisms of NO action unresolved.Herein, we demonstrate the inhibitory effect of NO on HIF-1␣ ubiquitination and interaction with pVHL. We present evidence that PHDs are targeted by NO, which suggests attenuation of prolyl hydroxylation as the underlying mechanism of NO-induced HIF-1␣ accumulation in normoxia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in some models of severe hypoxic stress, NO induces complete and reversible metabolic stasis required to survive the insult (19). The importance of NO in defending against ischemia is underscored by its regulation of the transcription factor hypoxia inducible factor 1, a master regulator of cellular homeostasis in the context of oxygen insufficiency (20).Coordination of energy supply and demand is mediated, in part, by NO activation of soluble guanylyl cyclase (sGC) and the associated accumulation of intracellular cGMP concentration ([cGMP] i ) (9,10,12,15,16,18), yet the mechanisms coordinating cGMP-dependent and metabolic signaling, beyond the production of NO, remain undefined. Recently, a novel mechanism was identified by which adenine nucleotides inhibit GCs (21,22) that is analogous to P site inhibition of adenylyl cyclases (23).…”
mentioning
confidence: 99%
“…Suppression of ROS fluxes can suppress the expression of both Mn-and Cu/Zn-SOD [78]. Moreover, the coordination of the whole set of regulatory events and its relation to oxygen partial pressure can be altered by variation of the cellular contents of the • NO radical, because this compound inhibits HIF-1α stabilization under hypoxia [52] or its oxidation under normal oxygenation [91], or, again, triggers GSH synthesis to change the redox environment and the control of gene expression [15].…”
Section: Mn-and Cu/zn-sod Induction and Controlmentioning
confidence: 99%